Structure and competitiveness of the rice sector in the Caribbean region (CFC/ACT Consortium [S.l.], 1993)
Provides the detailed analysis, conclusions and recommendations arrived at in proposing appropriate Common External Tariff (CET) rates for rice in the region. Summarises the major findings and recommendations.
Contents: v.1 summary of major findings and recommendations.- v.2. Data analysis and recommendations